Cold weather is a predisposing factor for testicular torsion in a tropical country: a retrospective study - Gomes, Daniel de Oliveira; Vidal, Rafael Rocha; Foeppel, Bruno Figueiredo; Faria, Danilo Fiorindo; Saito, Minori (São Paulo Medical Journal, 2015)
CONTEXT AND OBJECTIVE: Testicular torsion is a medical and urological emergency because it can lead to loss of the organ. The theory of seasonal testicular torsion occurrence is based on studies from institu-tions located in cold and temperate regions. The objective here was to determine whether cold weather is associated with higher incidence of testicular torsion in a tropical country, such as Brazil. DESIGN AND SETTING: Retrospective study, conducted in a tertiary and teaching hospital. METHODS: Patients with acute testicular torsion confirmed by surgery between April 2006 and March 2011 were studied. Information on weather conditions at the time of symptom onset was collected. RESULTS: A total of 64 testicular torsion cases were identified. The months with the highest incidences of testicular torsion were June (16%), July (19%) and August (11%), which had the lowest mean temperatures, of 17.6 °C, 16.4 °C and 18.2 °C, respectively. Eleven percent of cases occurred during spring (October to December), 16% occurred in summer (January to March), 34% occurred in fall (April to June) and 39% occurred in winter (July to September). There was a significant association between the incidence of tes-ticular torsion and the season (fall and winter), P < 0.001. CONCLUSIONS: Testicular torsion follows a seasonal association even in a tropical country, and is more frequent in the colder months of the year, namely fall and winter, when almost three-quarters of the cases occurred. These observations add further evidence that cold weather has an etiologic role in testicular torsion occurrence.